Genetic, physical and biochemical characterization of the Lipomyces kononenkoae alpha-amylase expressed in Saccharomyces cerevisiae - Steyn, Andries Johannes Christoffel,1963- (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D.) -- University of Stellenbosch, 1995.